P–329 Müllerian anomalies and embryo implantation in oocyte donation. (6th August 2021) - Muño. Muñoz, E; Fernandez, I; Cerrillo, M; Aguilar, J; Pellicer, A; Garrido, N
Abstract: Study question: Do patients with Mullerian anomalies (MA) who receive donated oocytes have different embryo implantation rate than patients with normal uterus? Summary answer: In oocyte donation, patients with MA had lower implantation rate than patients with normal uterus. What is known already: MA are associated with infertility and miscarriage but the mechanisms to explain this relation are not known. Some studies describe both oocyte and/or uterine factor. All studies describing the outcome in patients with MA, so far, are with own oocytes but none in oocyte donation. Study design, size, duration: A multicentre restrospective cohort study from January 2000 to December 2019. Patients receiving donated oocytes were divided between those with MA (n = 473) according ESHRE classification and other group with normal uterus (n = 57 869). The primary outcome was implantation rate at fresh embryo transfer. Secondary aims were biochemical pregnancy rate, clinical pregnancy rate, ongoing pregnancy rate, miscarriage rate and live pregnancy rate. Participants/materials, setting, methods: We considered the first oocyte donation cycle, without severe male factor, myomas, hydrosalpinx, Asherman syndrome, polyps or indication for preimplantational genetic diagnosis divided in two groups; patients with MA and no malformed uterus. MA group includes cycles of complete bicorporeal uterus (162), partial bicorporeal (30), bicorporeal septate (15), T shaped uterus (26), infantilis uterus (8), complete septate uterus (110), partial septate uterus (94) and hemi-uterus without rudimentary cavity (29). Main results and the role of chance: We registered 58 342 patients from our oocyte donation program. Results are shown as mean and 95%CI and differences in pregnancy rates were expressed as relative risks (RR) with 95% CI being reference patients with normal uterus. In patients with MA, the implantation rate was different according the categories being significantly lower in patients with unicornuate uterus (0.29 95%CI: 0.14–0.43. p = 0.03). Biochemical pregnancy rate was significantly higher in patients with septate uterus (RR 1.51 (95%CI 1.02–2.22, p = 0.03) and significantly lower in unicornuate uterus (RR 0.49 (95%CI 0.27–0.90). No differences were found in clinical pregnancy rate among groups, but ongoing pregnancy rate and live birth rate were lower in unicornuate uterus ( RR 0.28 (95%CI 0.13–0.63, p = 0.002), (RR 0.32 (95%CI 0.14–0.73, p = 0.007) respectively. Miscarriage rate was significantly higher in patients with septate uterus (RR 1.78 (95%CI 1.18–2.68, p = 0.006) Limitations, reasons for caution: As this was a retrospective cohort study, we were unable to study differences due to modifications in medical or laboratory protocols during this long period time. Different size of sample in some groups of MA makes impossible to translate conclusions to general population. Wider implications of the findings: Our results indicate that there might be a defect in the embryo implantation rate in patients with MA depending on uterine factor. Different sample size among groups and some groups with scarce number of cases make less precise results. More studies controlling biases are needed to confirm our results. Trial registration number: NCT04571671